The Protective Role of Maternal Immunization in Early Life - Cinicola, Bianca; Conti, Maria Giulia; Terrin, Gianluca; Sgrulletti, Mayla; Elfeky, Reem; Carsetti, Rita; Fernandez Salinas, Ane; Piano Mortari, Eva; Brindisi, Giulia; De Curtis, Mario; Zicari, Anna Maria; Moschese, Viviana; et al. (Frontiers in Pediatrics, 2021)
With birth, the newborn is transferred from a quasi-sterile environment to the outside world. At this time, the neonatal immune system is inexperienced and continuously subject to a process of development as it encounters different antigenic stimuli after birth. It is initially characterized by a bias towards T helper 2 phenotype, reduced T helper 1 and cytotoxic responses to microbial stimuli, low levels of memory and effector T and B cells and a high production of suppressive T regulatory cells. The aim of this setting, during fetal life, is to maintain an anti-inflammatory state and immune-tolerance. Maternal antibodies are transferred during pregnancy through the placenta and, in the first weeks of life of the newborn, they represent a powerful tool for protection. Thus, optimization of vaccination in pregnancy represents an important strategy to reduce the burden of neonatal infections and sepsis. Beneficial effects of maternal immunization are universally recognized, although the optimal timing of vaccination in pregnancy remains to be defined. Interestingly, the dynamic exchange that takes place at the fetal-maternal interface allows the transfer not only of antibodies, but also of maternal antigen presenting cells, probably in order to stimulate the developing fetal immune system in a harmless way. There are still controversial effects related to maternal immunization including the so called “immunology blunting”, i.e. a dampened antibody production following infant’s vaccination in those infants who received placentally transferred maternal immunity. However, clinical relevance of this phenomenon is still not clear. This review will provide an overview of the evolution of the immune system in early life and discuss the benefits of maternal vaccination. Current maternal vaccination policies and their rationale will be summarized on the road to promising approaches to enhance immunity in the neonate.